Exploring bedside clinical features of parkinsonism: A focus on differential diagnosis. (February 2019) - Bhidayasiri, Roongroj; Rattanachaisit, Watchara; Phokaewvarangkul, Onanong; Lim, Thien Thien; Fernandez, Hubert H.
Abstract: The proper diagnosis of parkinsonian disorders usually involves three steps: identifying core features of parkinsonism; excluding other causes; and collating supportive evidence based on clinical signs or investigations. While the recognition of cardinal parkinsonian features is usually straightforward, the appreciation of clinical features suggestive of specific parkinsonian disorders can be challenging, and often requires greater experience and skills. In this review, we outline the clinical features that are relevant to the differential diagnosis of common neurodegenerative parkinsonian disorders, including Parkinson's disease, multiple system atrophy, progressive supranuclear palsy, and corticobasal degeneration. We aim to make this process relatable to clinicians-in-practice, therefore, have categorised the list of clinical features into groups according to the typical sequence on how clinicians would elicit them during the examination, starting with observation of facial expression and clinical signs of the face, spotting eye movement abnormalities, examination of tremors and jerky limb movements, and finally, examination of posture and gait dysfunction. This review is not intended to be comprehensive. Rather, we have focused on the most common clinical signs that are potentially key to making the correct diagnosis and those that do not require special skills or training for interpretation. Evidence is also provided, where available, such as diagnostic criteria, consensus statements, clinicopathological studies or large multi-centre registries. Pitfalls are also discussed when relevant to the diagnosis. While no clinical signs are pathognomonic for certain parkinsonian disorders, certain clinical clues may assist in narrowing a differential diagnosis and tailoring focused investigations for the individual patient. Highlights: Differentiating PD from atypical parkinsonian disorders is a real clinical challenge. This article focuses on common clinical signs for assisting clinicians in the differential diagnosis. No clinical signs are pathognomonic for any parkinsonian disorders. Experiences and skills are required for the interpretation of these clinical signs.